A structured methodology for designing distributed algorithms for mobile entities - Cicerone, Serafino; Di Stefano, Gabriele; Navarra, Alfredo (Information sciences, 2021)
Following the wide investigation in distributed computing issues by mobile entities of the last two decades, we consider the need of a structured methodology to tackle the arisen problems. The aim is to simplify both the design of the resolution algorithms and the writing of the required correctness proofs. We would encourage the usage of a common framework in order to help both algorithm designers and reviewers in the intricate work of delivering and analyzing the proposed resolution strategies. We demonstrate the effectiveness and usefulness of the new methodology by highlighting various peculiarities arising in different scenarios. In particular, we consider two different tasks for asynchronous entities moving in the Euclidean plane and in graphs, respectively. We show how two resolution strategies have been designed by following the accurate guide dictated by the methodology. Furthermore, we also show how the corresponding correctness proofs are obtained.